Motivasi Kerja Pegawai Kecamatan Ganeas Kabupaten Sumedang - Suherman; Ai Rohaeni; Jeka Jaelani; Regita Dyah Iswara; Ujang Iwan R; Yane Sri Mulyani (LPPM UNSAP & FISIP UNSAP, 2022)
This research was carried out at the Ganeas Subdistrict Head Office, Sumedang Regency, West Java Province. The formulation of the problem in this administrative research practice is how the work motivation of employees at the Sub-district office of Ganeas, Sumedang Regency is, and how the efforts are made to increase employee motivation. The purpose of this research is to analyze the work motivation of employees at the subdistrict office of Ganeas Subdistrict, Sumedang Regency, as well as to find out what efforts are being made to increase employee motivation in the Ganeas subdistrict environment. This type of research is qualitative research. The data collection technique used is qualitative data collection, namely by reasoning the variables studied qualitatively in the form of information obtained from qualitative informants without using statistics. The research location is at the Subdistrict Head Office of Ganeas, Sumedang Regency. From this research, the research informant is Mr. Camat, an employee at the Ganeas Sub-district Head's office. The result of this research is that the work motivation of the Ganeas Subdistrict Head office, Sumedang Regency is categorized as good but there are still some things that need to be improved, therefore the author hopes that the Ganeas Subdistrict Camat will be able to improve employee performance so that it is even better supported by the provision of motivation appropriate so that employees at the Ganeas sub-district office can increase their work motivation well and maximally. The conclusion of this study is that the work motivation of the sub-district office employees of Ganeas Subdistrict, Sumedang Regency is categorized as good but there are still some things that need to be improved because there are still workers who are not on time at work and from the level of discipline of these employees. Suggestions from the author are expected to the leadership at the subdistrict office of Ganeas subdistrict, Sumedang regency, in order to increase work motivation and work quality of employees at the subdistrict office of Ganeas subdistrict, Sumedang regency, West Java province.